The "Common Pool" Problems in the Protected Area Regarding Natural Tourism in Indonesia - Badi'ah; Hariadi Kartodihardjo; Bramasto Nugroho; Bambang Supriyanto (Jurnal Manajemen Hutan Tropika, 2022)
Phenomena that indicate the performance of the use of natural tourism in protected areas indicate that there are institutional problems in it. This study aims to determine the influence of exogenous variables on the action arena for the use of natural tourism in protected areas in Indonesia. Data were collected through in-depth interviews, participatory observation, document, and regulatory review. Then the data were analyzed using descriptive analysis. This study was analyzed using the institutional analysis and development (IAD) framework. This framework provides a useful approach to understanding institutional issues. Based on the research, the influence of exogenous variables on the action arena, among others 1) there is an incorrect implementation between the cooperation agreement and the permit carried out by the Mount Gede Pangrango National Park Office as the principal, which has resulted in the agent bearing additional costs to obtain exclusion rights, and the principal's loss does not receive a contribution in the form of Levies on The Results of Business Activities for Nature Tourism Facilities from the transfer of rights to agents; 2) when public access is closed in the public space, there will be a conflict between the agent and the community which creates a high cost of exclusion and is charged to the agent; 3) the agent is aware of the lack of principal resources to carry out supervision so that the agent does not immediately carry out his obligations.